Implementasi Pembelajaran Kontekstual pada Mata Pelajaran Fikih di MTsN 7 Kepung Kediri - Khafidhotun Nasikhah; Badrus Badrus (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2020)
This article discusses the implementation of contextual learning in fiqh subjects at MTsN 7 Kepung Kediri. This research is a qualitative research with a phenomenological approach that focuses on implementation, evaluation models, contextual learning outcomes in fiqh subjects. The results of the study, (1) The implementation of contextual learning in fiqh subjects was carried out in several stages, namely, constructing, inquiry, questionnaire, creating a learning community, modeling, reflection and authentic assessment; (2) The evaluation model uses the Stake's Countenance Model; (3) The learning outcomes of the study, namely, students can understand the principles of Islamic laws in detail regarding food and drink, and gain meaningful knowledge in fiqh learning, inculcate Islamic legal values such as the formation of spiritual values and skills, students can distinguish between halal and haram food and beverages, formed a strong learning motivation, become a student who is responsible, tolerant, and disciplined, and fosters honest, polite, and self-confident.